Toxicidade de organocalcogênios e seus mecanismos através da expressão gênica em leucócitos humanos - Bueno, Diones Caeran (2015)
Selenium (Se) is an essential micronutrient present in selenoproteins on living beins, in the form of the amino acid selenocysteine and selenomethionine. Chemically related to Se, tellurium (Te) has no biological function in mammals, however, organic Te compounds showed up as good antioxidant agents. Although ebselen (Ebs), diphenyl diselenide [(PhSe)2] and diphenyl ditelluride [(PhTe)2] present antioxidant properties via their glutathione peroxidase (GPx) mimetic activity, these compounds exhibit toxic effects at high concentrations due to its property in oxidizing thiols groups. However, the toxicity mechanism of these compounds through the modulation of gene expression was never studied in human cells. Thus, this study aimed to evaluate the cytotoxicity and genotoxicity of organochalcogens in human leukocytes, and evaluate their mechanisms through the production of reactive oxygen species (ROS) and modulation of antioxidant proteins expression, and to evaluate the relative amount of organochalcogens in contact with the cells in our ex vivo exposure model. Trypan s blue exclusion test and comet assay were used to evaluate, respectively, cytotoxicity and genotoxicity induced by the compounds. The fluorescence of dichlorofluorescein (DCFH) and propidium iodide (PI) were measured in leukocytes exposed by flow cytometry. The expression of the genes for the enzymes Catalase, Superoxide Dismutase 1, Glutathione Peroxidase 3, Glutathione Peroxidase 4, Thioredoxin Reductase 1 and Nrf-2 were analyzed. A dichloromethane extraction of the buffer and the pellet of the cells was injected into a GC-MS apparatus to evaluate the amount of compound in contact with cells. The compounds induced a reduction in cell viability only in the concentration of 50 μM, being Ebs the most cytotoxic compound, followed by (PhTe)2 and (PhSe)2, while (PhTe)2 was the only compound able of increasing the apoptotic rate of leukocytes, which happened at all concentrations (10-50 μM). (PhTe)2 increased DNA damage index in all tested concentrations (5-50 μM), while Ebs and (PhSe)2 did it only at 50 μM concentration. Surprisingly, (PhSe)2 was the only compound effective in increasing ROS production in all tested concentrations (10-50 μM), which was accompanied by an increase in the SOD1 expression and a decrease in CAT expression. All compounds were effective in decreasing the expression of GPX3 and NFE2L2 (Ebs > (PhTe)2 > (PhSe)2), and none altered the expression of GPX4 and TRXR1. The compounds were found in higher concentrations in leukocyte pellet extraction than in their buffer. We conclude that the toxicity of the compounds in question is not directly related to their property in inducing production of ROS.